Matrix metalloproteinase‐9 mediated shedding of syndecan‐4 in glomerular endothelial cells. (22nd February 2019) - Reine, Trine M.; Lanzalaco, Francesca; Kristiansen, Oddrun; Enget, Anne Randi; Satchell, Simon; Jenssen, Trond G.; Kolset, Svein O.
Abstract: Background: Diabetic nephropathy is the most common cause of end‐stage renal failure in the western world and Asia. The mechanisms are not fully elucidated, but disruption of glomerular endothelial glycocalyx and shedding of its components including syndecans has been implicated. Aims: We hypothesize that reduced glomerular filtration in diabetes is caused by disruption of endothelial glycocalyx in glomeruli, including increased shedding of syndecan‐4. The aim of this study was to determine the effects of experimental diabetic conditions by means of hyperglycemia and IL‐1β exposure on syndecan‐4 shedding in GEnC, and to investigate regulation of shedding by sheddases. Results: We found that in GEnC the expression of syndecan‐4 is higher than that of the other syndecans. In polarized GEnC, apical shedding of syndecan‐4 and syndecan‐4 gene expression was increased by 60% after IL‐1β‐stimulation, but not affected by hyperglycemic conditions. This was accompanied by a 50% increase in MMP9 gene expression in IL‐1β‐stimulated cells but not hyperglycemia. MMP9 knockdown reduced syndecan‐4 shedding by 50%. Conclusion: IL‐1β but not hyperglycemia increases the shedding of syndecan‐4 from GEnC in an MMP9‐dependent manner. This provides a potential mechanism of GEnC damage in diabetes and other inflammatory conditions.